2008
DOI: 10.1890/07-0465.1
|View full text |Cite
|
Sign up to set email alerts
|

Angler Numerical Response Across Landscapes and the Collapse of Freshwater Fisheries

Abstract: Recreational angling opportunities in lakes are distributed across landscapes and attract anglers based on the combination of angling quality, travel distance, and availability of facilities. The relationship between angler density and fishing quality, as measured by catch rate, represents a numerical response that is analogous to a predator numerical response to variability in prey abundance. We quantified this numerical response of anglers to rainbow trout, Oncorhynchus mykiss, populations distributed over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
265
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(287 citation statements)
references
References 34 publications
19
265
2
1
Order By: Relevance
“…Our finding that anglers visited lakes that were within a reasonable driving distance of large population centers is nothing new; it is consistent with conventional data from Alberta and well established in the literature (e.g., Post et al 2008;Ward et al 2013). However, the fact that we observed angler preferences (and movement networks) by applying fairly basic analyses to data from the uncoordinated use of an app that was not developed for research demonstrates the enormous potential of this technology.…”
Section: Discussionsupporting
confidence: 89%
“…Our finding that anglers visited lakes that were within a reasonable driving distance of large population centers is nothing new; it is consistent with conventional data from Alberta and well established in the literature (e.g., Post et al 2008;Ward et al 2013). However, the fact that we observed angler preferences (and movement networks) by applying fairly basic analyses to data from the uncoordinated use of an app that was not developed for research demonstrates the enormous potential of this technology.…”
Section: Discussionsupporting
confidence: 89%
“…It is often assumed that anglers are highly mobile and are responsive to spatial (among waterbodies) and temporal (among years) differences in fish abundances (Johnson and Carpenter, 1994;Carpenter and Brock, 2004;Post, et al, 2008). We expected 20-25% of angler parties to move among the lakes during a single trip, but the percentage of angling parties that moved among lakes was less than expected.…”
Section: Discussionmentioning
confidence: 78%
“…The factors involved in the decision to move from one lake to another was unclear, although it may be related to catch as a majority of the parties that moved did not catch any fish at their first location. However, catch is often not the primary motivation for angling (Driver and Knopf, 1976;Fedler and Ditton, 1994) and the decision to move to another lake may be related to other noncatch-related factors (Johnson and Carpenter, 1994;Hunt, 2005;Post et al, 2008;Johnston et al, 2010;Hunt et al, 2011). For example, Johnston et al (2011) observed that trout anglers were not attracted to high-catch-rate fisheries and they suggested that angler behaviour is complex and may be strongly influenced by harvest regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, earlier research has emphasized that angler effort responses are determined by multiple catch and non-catch related factors, including angling regulations (Aas et al, 2000;Oh et al, 2005;Hunt, 2005), and are not simply linked to fishing successes alone (Johnson and Carpenter, 1994;Hunt, 2005;Post et al, 2008;Johnston et al, 2010;Hunt et al, in press). In particular, harvest regulations may alter the attractiveness of a fishery if they are perceived to constrain anglers' opportunities to harvest fish (Radomski and Goeman, 1996;Dorr et al, 2002;, or if they alter anglers' expectations about the fishery Cook et al, 2001;Beard et al, 2003).…”
Section: Discussionmentioning
confidence: 99%